178k views
2 votes
3(x + 4) = 2(x -7)

math

User Hargrovm
by
5.0k points

2 Answers

6 votes

Answer:

Hi there!

Your answer is:

x= -26

Explanation:

3(x+4) = 2(x-7)

First, distribute 3 to the first parentheses and 2 to the second parentheses.

3x +12 = 2x-14

Next, get all whole numbers on the right side

3x +12 = 2x-14

-12

3x = 2x -26

Then, get all the X's on the left side

3x = 2x -26

-2x

x= -26

Hope this helps

User Inbal
by
4.6k points
1 vote

Answer:

x=-26

Explanation:

User Antoine Mottier
by
4.8k points